Plant Origin of Green Propolis: Bee Behavior, Plant Anatomy and Chemistry. Issue 1 (2005) - Teixeira, Érica Weinstein; Negri, Giuseppina; Meira, Renata M. S. A.; Message, Dejair; Salatino, Antonio
Abstract : Propolis, a honeybee product, has gained popularity as a food and alternative medicine. Its constituents have been shown to exert pharmacological effects, such as anti-microbial, anti-inflammatory and anticancer. Shoot apices of Baccharis dracunculifolia (alecrim plant, Asteraceae) have been pointed out as sources of resin for green propolis. The present work aimed (i) to observe the collecting behavior of bees, (ii) to test the efficacy of histological analysis in studies of propolis botanical origin and (iii) to compare the chemistries of alecrim apices, resin masses and green propolis. Bee behavior was observed, and resin and propolis were microscopically analyzed by inclusion in methacrylate. Ethanol extracts of shoot apices, resin and propolis were analyzed by gas chromatography/mass spectroscopy. Bees cut small fragments from alecrim apices, manipulate and place the resulting mass in the corbiculae. Fragments were detected in propolis and identified as alecrim vestiges by detection of alecrim structures. Prenylated and non-prenylated phenylpropanoids, terpenoids and compounds from other classes were identified. Compounds so far unreported for propolis were identified, including anthracene derivatives. Some compounds were found in propolis and resin mass, but not in shoot apices. Differences were detected between male and female apices and, among apices, resin and propolis. Alecrim apices are resin sources for green propolis. Chemical composition of alecrim apices seems to vary independently of season and phenology. Probably, green propolis composition is more complex and unpredictable than previously assumed.